The Settler and the Land: Using Patrick Wolfe’s logic of elimination to understand frontier violence in Australia’s colonial era (NEW: Emerging scholars in Australian Indigenous Studies, 2018)
Whilst it is the heinous acts of physical violence that are often foregrounded when imagining frontier violence, it is the structural forces of colonialism that have had a continued effect on Aboriginal culture and identity. This essay will discuss the legitimacy of Patrick Wolfe’s logic of elimination in the face of frontier violence, examining the more insidious ways in which colonialism manifests itself in modern Australia.Keywordssettler colonialism; frontier violence; Indigenous dispossession